Recognising and rewarding teaching : Australian teaching criteria and standards and expert peer review : final report. - Chalmers, Denise (Australia. Dept of Education and Training (DET), 2019)
Despite decades of arguing for the importance of recognising and rewarding quality teaching and the provision of a quality learning experience for students, higher education institutions have not always made the critical link between the two. Consequently, they have made little headway towards building effective processes of rewarding and recognising quality teaching. It should therefore not be surprising that governments and major stakeholders in the sector continue to express concern about the quality of teaching in our higher education institutions. The commitment of tertiary institutions to reward and recognise teaching has been elusive, despite progress being made in the development of teaching criteria and the identification of appropriate evidence of teaching excellence. The fellowship program was targeted primarily at institutions and the Australian tertiary sector and to support individuals within the institutions to implement and embed criteria and standards in policy and practice. International interest in the framework and the fellowship program enabled the concepts to be trialled across several countries and cultural settings. The fellowship program was able to demonstrate that university teaching could be enhanced, rewarded and recognised in a manner that sustains a focus on teaching that delivers quality student learning experiences. It is estimated that over 3200 individuals were engaged with the work of the fellowship through direct participation and communication and attendance at presentations, workshops and meetings. No attempt has been made to estimate the number who might have engaged through the publications and through accessing the website and other secondary sources. In terms of number of institutions that have engaged in the fellowship activities, it is estimated that 60 Australian higher education institutions were involved, with the majority being universities. Internationally, more than 230 international institutions were involved through direct communication and/or participation in presentations and workshops through the fellowship program 2015-2018. [Executive summary, ed]